Nickel-chromium alloy etching agent and nickel-chromium alloy grain corrosion display method

By using a mixed solution of hydrofluoric acid, nitric acid and water as the etching agent of nickel-chromium alloy, the problem of difficult to display the metallographic structure of nickel-chromium alloy in the prior art is solved, and clear grain display and wide metallographic display range are achieved, which improves the accuracy of product analysis and process stability.

CN119595398AActive Publication Date: 2025-03-11KONFOONG MATERIALS INTERNATIONAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411728695.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-11
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively display the metallographic structure of nickel-chromium alloys, especially when the grinding requirements of nickel-chromium alloys are high, it is impossible to clearly display the grain and grain boundaries.

Method used

A mixed solution of hydrofluoric acid, nitric acid and water is used as the etchant for nickel-chromium alloy. The volume ratio of hydrofluoric acid:nitric acid:water is 1: (9-11): (18-22). The grain and metallographic structure of nickel-chromium alloy are shown by chemical corrosion.

Benefits of technology

It realizes clear display of nickel-chromium alloy grains, has a wide metallographic display range, more accurate product analysis, stable process and reusable, short detection time, effectively avoiding the generation of unqualified products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119595398A_ABST
    Figure CN119595398A_ABST
Patent Text Reader

Abstract

The invention provides a nichrome etching agent and a nichrome grain corrosion display method, the nichrome etching agent comprises a mixed solution of hydrofluoric acid, nitric acid and water, and the volume ratio of hydrofluoric acid to nitric acid to water is 1: (9-11): (18-22). When the nickel-chromium alloy etchant is used for chemical corrosion, crystal grains are clearly displayed, the metallographic display range is wide, product analysis is more accurate, the process is stable and simple, the nickel-chromium alloy etchant can be repeatedly used, the detection time is short, a result can be quickly obtained, and unqualified products are effectively prevented from being produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material corrosion, and in particular to a nickel-chromium alloy etchant and a method for displaying grain corrosion of the nickel-chromium alloy. Background Art

[0002] The internal structure of metal materials is directly and closely related to material properties such as hardness, strength, and ductility, and metallographic observation is the most direct and effective method to study the internal structure of metal materials. Metallography refers to the chemical composition of metals or alloys and the physical and chemical states of various components inside the alloy. In the field of metal materials, the principle of quantitative metallography is generally used to determine the three-dimensional spatial morphology of metallographic structures, and the quantitative relationship between components, structures, and properties is established based on the three-dimensional spatial morphology to obtain metal materials with characteristic properties. The principle of quantitative metallography is to measure and calculate the metallographic microstructure of the metallographic sample grinding surface or metallographic sample film to determine the three-dimensional spatial morphology of the metallographic structure.

[0003] To conduct metallographic observation, the metal grains must first be displayed, and then the metallographic structure of the metal must be observed using a metallographic microscope. Even if the metal material is very small, it still contains many small crystals inside. Since these small crystals with basically the same lattice phase are irregular in shape and granular, they are called "grains". The size and shape of the grains have a significant impact on the performance of the material. Generally, the finer and more uniform the grains, the better the overall performance of the material. The grain boundary in the metallographic structure is the interface between crystals with the same structure but different orientations. On the crystal interface, the atomic arrangement transitions from one orientation to another, so the atomic arrangement at the grain boundary is in a transitional state. Metal grain boundaries are generally made visible by using etching methods, which are extremely important for studying the internal organizational structure of materials.

[0004] With the development of science and technology, the demand for alloy metals in industrial production is increasing day by day. For new alloy materials, new metallographic structure research methods are needed. Nickel-chromium alloy is a highly corrosion-resistant alloy material. To fully display the metallographic structure of nickel-chromium alloy, suitable etchants and display methods are needed. There is very little corrosion data on nickel-chromium alloy metallographic specimens, and there are many deficiencies in the corrosion based on the preparation method of nickel-chromium alloy metallographic solution and the preparation ratio of various etchants. The metallographic specimens of nickel-chromium alloy are corroded by etchants prepared in a certain proportion of nitric acid and water or nitric acid, hydrochloric acid and water. First, the corrosion time is long, and second, the corrosion effect is not obvious, and no clear metallographic structure can be seen. The grain boundaries between grains in the metallographic structure are not clear; if the nitric acid or the ratio of nitric acid to hydrochloric acid is increased, over-corrosion is formed, and the grain boundaries and grains appear black, and no clear metallographic structure can be observed. Therefore, in order to observe a clear metallographic structure and make different phases have obvious boundaries and contrasts, the preparation of the etchant is extremely critical.

[0005] CN 104513985 A discloses a nickel-chromium alloy metallographic etching liquid and an etching method. The etching liquid is a mixed solution of concentrated nitric acid, concentrated hydrochloric acid, glacial acetic acid and water, wherein the volume ratio of concentrated nitric acid, concentrated hydrochloric acid, glacial acetic acid and water in the mixed solution is 1:1:1:1. The etching method comprises: dropping the etching liquid on the etching surface of the nickel-chromium alloy metallographic sample after grinding and polishing, the etching liquid is immersed in the sample to a depth of 1-2 mm, and the etching time is 10s-10min; rinsing the sample surface with distilled water for more than 2 minutes; rinsing the sample surface with alcohol, and then wiping the sample surface with absorbent cotton with alcohol.

[0006] CN 106501058 A discloses a nickel-chromium alloy etchant and a metallographic structure display method of the nickel-chromium alloy. The etchant comprises a mixed solution of nitric acid and hydrochloric acid; the volume ratio of the nitric acid to the hydrochloric acid is 1:1, the concentration of the nitric acid is 65wt%, and the concentration of the hydrochloric acid is 36wt%; the metallographic structure display method comprises the following steps: grinding the nickel-chromium alloy; mechanically polishing the ground nickel-chromium alloy; immersing the polished nickel-chromium alloy in the etchant for corrosion, and drying.

[0007] However, when the grinding requirements for nickel-chromium alloy are high, the grinding surface must be free of scratches and one part of the product must be exposed to the air while the other part is soaked during infiltration. When taking a picture, the junction of the two surfaces has metallographic display, while the rest of the display is not obvious. Therefore, it is still necessary to develop a new type of nickel-chromium alloy etchant and a method for displaying grain corrosion of nickel-chromium alloy. Summary of the invention

[0008] In view of the problems existing in the prior art, the present invention provides a nickel-chromium alloy etchant and a method for displaying grain corrosion of nickel-chromium alloy, wherein the nickel-chromium alloy etchant comprises a mixed solution of hydrofluoric acid, nitric acid and water, and the volume ratio of hydrofluoric acid: nitric acid: water is 1: (9-11): (18-22). The nickel-chromium alloy etchant is used for chemical corrosion, and the grain display is clear, the metallographic display range is wide, the product analysis is more accurate, the process is stable and simple and can be reused, the detection time is short, the results can be obtained quickly, and the generation of defective products is effectively avoided.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] One of the purposes of the present invention is to provide a nickel-chromium alloy etchant, which comprises a mixed solution of hydrofluoric acid, nitric acid and water, and the volume ratio of hydrofluoric acid: nitric acid: water is 1: (9-11): (18-22).

[0011] In the present invention, the volume ratio of hydrofluoric acid: nitric acid: water is 1: (9-11): (18-22), for example 1:9:18, 1:9:20, 1:9:22, 1:10:18, 1:10:20, 1:10:22, 1:11:18, 1:11:20 or 1:11:22, etc.

[0012] Nickel-chromium alloy is an alloy with corrosion resistance. If the corrosiveness of the corrosive agent is low, the metallographic structure of the nickel-chromium alloy cannot be fully displayed; if the corrosiveness of the corrosive agent is high, the metallographic structure of the nickel-chromium alloy is excessively corroded, which will also affect the display effect of the metallographic structure of the nickel-chromium alloy. Therefore, the nickel-chromium alloy etchant of the present invention includes a mixed solution of hydrofluoric acid, nitric acid and water, and the concentration and volume ratio of hydrofluoric acid, nitric acid and water are strictly limited. It can moderately corrode the surface of the nickel-chromium alloy, thereby fully displaying the metallographic structure of the nickel-chromium alloy.

[0013] As a preferred technical solution of the present invention, the concentration of the hydrofluoric acid is 35-45wt%, for example, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, 41wt%, 42wt%, 43wt%, 44wt% or 45wt%, etc., and the concentration of the nitric acid is 65-68wt%, for example, 65wt%, 66wt%, 67wt% or 68wt%, etc.

[0014] It should be noted that the water used to prepare the nickel-chromium alloy etchant can be tap water.

[0015] The second object of the present invention is to provide a method for displaying grain corrosion of nickel-chromium alloy using the nickel-chromium alloy etchant described in the first object, wherein the method for displaying grain corrosion comprises the following steps:

[0016] The nickel-chromium alloy is sequentially subjected to grinding, electrolytic polishing, primary cleaning, chemical etching, secondary cleaning, and drying; wherein the chemical etching uses the nickel-chromium alloy etchant.

[0017] In the present invention, the area after electrolytic polishing can be imaged, the image-taking area is large, the product analysis is more accurate and the grinding requirement is relatively low.

[0018] As a preferred technical solution of the present invention, the polishing includes: polishing the nickel-chromium alloy on 240# water-based sandpaper and 1000# water-based sandpaper in sequence, using water as a wetting agent.

[0019] As a preferred technical solution of the present invention, the grinding time is 5-10 minutes, for example, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes.

[0020] As a preferred technical solution of the present invention, the electrolyte used in the electrolytic polishing includes a mixed solution of ethanol, 2-butoxyethanol and perchloric acid, and the volume ratio of ethanol: 2-butoxyethanol: perchloric acid is x:y:z=(0.65-0.75):(0.05-0.15):(0.15-0.25), x+y+z=1; wherein the concentration of the ethanol is 95wt%, and the concentration of the perchloric acid is 30wt%.

[0021] In the present invention, the volume ratio of ethanol:2-butoxyethanol:perchloric acid is x:y:z=(0.65-0.75):(0.05-0.15):(0.15-0.25), x+y+z=1, for example 0.65:0.15:0.2, 0.65:0.1:0.25, 0.7:0.1:0.2, 0.7:0.15:0.15, 0.75:0.05:0.2 or 0.75:0.1:0.15, etc.

[0022] As a preferred technical solution of the present invention, the voltage of the electrolytic polishing is 35-40V, such as 35V, 36V, 37V, 38V, 39V or 40V.

[0023] As a preferred technical solution of the present invention, the electrolytic polishing time is 50-100s, for example, 50s, 60s, 70s, 80s, 90s or 100s.

[0024] As a preferred technical solution of the present invention, the chemical corrosion includes: using the nickel-chromium alloy etchant, dripping it on the electrolytic polishing area of ​​the nickel-chromium alloy, and staying for 60-90s, such as 60s, 65s, 70s, 75s, 80s, 85s or 90s.

[0025] As a preferred technical solution of the present invention, the grain corrosion display method comprises the following steps:

[0026] The nickel-chromium alloy is sequentially subjected to grinding, electrolytic polishing, primary cleaning, chemical etching, secondary cleaning, and drying;

[0027] The polishing comprises: polishing the nickel-chromium alloy on 240# water-based sandpaper and 1000# water-based sandpaper in sequence, using water as a wetting agent, and the polishing time is 5-10min; the electrolyte used in the electrolytic polishing comprises a mixed solution of ethanol, 2-butoxyethanol and perchloric acid, and the volume ratio of ethanol: 2-butoxyethanol: perchloric acid is x:y:z=(0.65-0.75):(0.05-0.15):(0.15-0.25), x+y+z=1; the concentration of the ethanol is 95wt%, and the concentration of the perchloric acid is 30wt%; the voltage of the electrolytic polishing is 35-40V, and the time is 50-100s; the chemical corrosion adopts the nickel-chromium alloy etchant; the chemical corrosion comprises: using the nickel-chromium alloy etchant, dripping it on the electrolytic polishing area of ​​the nickel-chromium alloy, and staying for 60-90s.

[0028] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0029] The present invention provides a nickel-chromium alloy etchant and a method for displaying grain corrosion of nickel-chromium alloy, wherein the nickel-chromium alloy etchant comprises a mixed solution of hydrofluoric acid, nitric acid and water, and the volume ratio of hydrofluoric acid: nitric acid: water is 1: (9-11): (18-22). The nickel-chromium alloy etchant is used for chemical corrosion, and the grains are clearly displayed, the metallographic display range is wide, the product analysis is more accurate, the process is stable and simple and can be reused, the detection time is short, the results can be obtained quickly, and the generation of defective products is effectively avoided. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a metallographic microscope photograph observed in Example 1 of the present invention;

[0031] Figure 2 is a metallographic microscope photograph observed in Example 2 of the present invention;

[0032] Figure 3 is a metallographic microscope photograph observed in Example 3 of the present invention;

[0033] Figure 4 is a metallographic microscope photograph observed in Example 4 of the present invention;

[0034] Figure 5 is a metallographic microscope photograph observed in Example 5 of the present invention;

[0035] Figure 6 is a metallographic microscope photograph observed in Example 6 of the present invention;

[0036] Figure 7 is a metallographic microscope photograph observed in Example 7 of the present invention;

[0037] Figure 8is a metallographic microscope photograph observed in Example 8 of the present invention;

[0038] Fig. 9 is a metallographic microscope photograph observed in Example 9 of the present invention;

[0039] Fig.10 This is a metallographic microscope photo observed in Comparative Example 1 of the present invention;

[0040] Fig.11 It is a metallographic microscope photograph observed in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0042] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, typical but non-limiting embodiments of the present invention are as follows:

[0043] Example 1

[0044] The present embodiment provides a method for displaying grain corrosion of a nickel-chromium alloy, comprising polishing, electrolytic polishing, primary cleaning, chemical etching, secondary cleaning, and drying in sequence; the nickel-chromium alloy etchant formula used in the chemical etching is: 40wt% hydrofluoric acid: 65wt% nitric acid: water in a volume ratio of 1:10:20; the electrolyte formula used in the electrolytic polishing is: 95wt% ethanol: 2-butoxyethanol: 30wt% perchloric acid in a volume ratio of 7:1:2;

[0045] The method for displaying grain corrosion of nickel-chromium alloy comprises the following steps:

[0046] (1) First, the nickel-chromium alloy was polished on 240# and 1000# water-based sandpaper in turn for 8 minutes, using water as a wetting agent until the surface was bright.

[0047] (2) Put the polished nickel-chromium alloy into an electrolytic polishing machine, use a homemade electrolyte, electrolytic polish at 36 V for 50 seconds, then take it out and wash it with clean water;

[0048] (3) Use a homemade nickel-chromium alloy etchant, drop it on the electrolytic polishing area of ​​the nickel-chromium alloy, leave it for 70 seconds, and then wash it with clean water;

[0049] (4) After the nickel-chromium alloy is blown dry, it is placed in a metallographic microscope to observe the metallographic structure and take a picture for analysis.

[0050] The metallographic microscope photos observed in this embodiment are as follows Figure 1As shown, it can be seen that the metallographic structure of the nickel-chromium alloy in this embodiment has a good display effect, and the black spots are product defects, not excessive corrosion of the metallographic structure.

[0051] Example 2

[0052] The present embodiment provides a method for displaying grain corrosion of a nickel-chromium alloy, comprising polishing, electrolytic polishing, primary cleaning, chemical etching, secondary cleaning, and drying in sequence; the nickel-chromium alloy etchant formula used in the chemical etching is: 40wt% hydrofluoric acid: 65wt% nitric acid: water in a volume ratio of 1:9:18; the electrolyte formula used in the electrolytic polishing is: 95wt% ethanol: 2-butoxyethanol: 30wt% perchloric acid in a volume ratio of 7:1:2;

[0053] The method for displaying grain corrosion of nickel-chromium alloy comprises the following steps:

[0054] (1) First, the nickel-chromium alloy was polished on 240# and 1000# water-based sandpaper in turn for 5 minutes, using water as a wetting agent until the surface was bright.

[0055] (2) Put the polished nickel-chromium alloy into an electrolytic polishing machine, use a homemade electrolyte, electrolytic polish at 36 V for 50 seconds, then take it out and wash it with clean water;

[0056] (3) Use a homemade nickel-chromium alloy etchant, drop it on the electrolytic polishing area of ​​the nickel-chromium alloy, leave it for 60 seconds, and then wash it with clean water;

[0057] (4) After the nickel-chromium alloy is blown dry, it is placed in a metallographic microscope to observe the metallographic structure and take a picture for analysis.

[0058] The metallographic microscope photos observed in this embodiment are as follows Figure 2 As shown, it can be seen that the metallographic structure of the nickel-chromium alloy in this embodiment has a good display effect.

[0059] Example 3

[0060] The present embodiment provides a method for displaying grain corrosion of a nickel-chromium alloy, comprising polishing, electrolytic polishing, primary cleaning, chemical etching, secondary cleaning, and drying in sequence; the nickel-chromium alloy etchant formula used in the chemical etching is: hydrofluoric acid with a concentration of 40wt%: nitric acid with a concentration of 65wt%: water in a volume ratio of 1:11:22; the electrolyte formula used in the electrolytic polishing is: ethanol with a concentration of 95wt%: 2-butoxyethanol: perchloric acid with a concentration of 30wt% in a volume ratio of 7:1:2;

[0061] The method for displaying grain corrosion of nickel-chromium alloy comprises the following steps:

[0062] (1) First, the nickel-chromium alloy was polished on 240# and 1000# water-based sandpaper in turn for 10 min, using water as a wetting agent until the surface was bright.

[0063] (2) Put the polished nickel-chromium alloy into an electrolytic polishing machine, use a homemade electrolyte, electrolytic polish at 36 V for 50 seconds, then take it out and wash it with clean water;

[0064] (3) Use a homemade nickel-chromium alloy etchant, drop it on the electrolytic polishing area of ​​the nickel-chromium alloy, leave it for 90 seconds, and then wash it with clean water;

[0065] (4) After the nickel-chromium alloy is blown dry, it is placed in a metallographic microscope to observe the metallographic structure and take a picture for analysis.

[0066] The metallographic microscope photos observed in this embodiment are as follows Figure 3 As shown, it can be seen that the metallographic structure of the nickel-chromium alloy in this embodiment has a good display effect.

[0067] Example 4

[0068] The present embodiment provides a method for displaying grain corrosion of a nickel-chromium alloy. Compared with the embodiment 1, the only difference is that the electrolytic polishing in step (2) is replaced by mechanical polishing. Specifically, the nickel-chromium alloy polished with 1000# water-based sandpaper is further polished with 1500# water-based sandpaper for 10 minutes, and water is used as a wetting agent to polish until the surface is bright.

[0069] The metallographic microscope photos observed in this embodiment are as follows Figure 4 As shown, it can be seen that there are no grains and the entire surface is covered with grinding scratches.

[0070] Example 5

[0071] This embodiment provides a method for displaying grain corrosion of nickel-chromium alloy. Compared with Example 1, the only difference is that the electrolyte formula used in electropolishing is adjusted to a volume ratio of 95wt% ethanol: 2-butoxyethanol: 30wt% perchloric acid of 6:2:2.

[0072] The metallographic microscope photos observed in this embodiment are as follows Figure 5 As shown, it can be seen that the electrolyte can polish the product, but the grain display is poor.

[0073] Example 6

[0074] This embodiment provides a method for displaying grain corrosion of nickel-chromium alloy. Compared with embodiment 1, the only difference is that in step (2), after electrolytic polishing at a voltage of 30 V for 100 s, the alloy is taken out and washed with clean water.

[0075] The metallographic microscope photos observed in this embodiment are as follows Figure 6 As shown, it can be seen that the product can be polished under the voltage and time of electrolytic polishing, but the grain appearance is poor.

[0076] Example 7

[0077] This embodiment provides a method for displaying grain corrosion of nickel-chromium alloy. Compared with embodiment 1, the only difference is that in step (2), after electrolytic polishing at a voltage of 45 V for 40 seconds, the alloy is taken out and washed with clean water.

[0078] The metallographic microscope photos observed in this embodiment are as follows Figure 7 As shown, it can be seen that the product can be polished under the voltage and time of electrolytic polishing, but the grain appearance is poor.

[0079] Example 8

[0080] This embodiment provides a method for displaying grain corrosion of nickel-chromium alloy. Compared with Embodiment 1, the only difference is that in step (3), the residence time is reduced to 50 seconds.

[0081] The metallographic microscope photos observed in this embodiment are as follows Figure 8 As shown, it can be seen that the corrosion time in the nickel-chromium alloy etchant is relatively short, which will result in the grain boundaries of the metallographic structure of the nickel-chromium alloy not being displayed at all. The metallographic structure display effect of the nickel-chromium alloy in this embodiment is relatively poor.

[0082] Example 9

[0083] This embodiment provides a method for displaying grain corrosion of nickel-chromium alloy. Compared with Embodiment 1, the only difference is that in step (3), the residence time is increased to 100 s.

[0084] The metallographic microscope photos observed in this embodiment are as follows Fig. 9 As shown, it can be seen that a long corrosion time in the nickel-chromium alloy etchant will lead to excessive corrosion of the metallographic structure of the nickel-chromium alloy and corrosion of part of the grain boundaries. The metallographic structure display effect of the nickel-chromium alloy in this comparative example is poor.

[0085] Comparative Example 1

[0086] This comparative example provides a method for displaying grain corrosion of a nickel-chromium alloy. Compared with Example 1, the only difference is that the formula of the nickel-chromium alloy etchant used for chemical corrosion is adjusted, and the volume ratio of hydrofluoric acid with a concentration of 40wt%: nitric acid with a concentration of 65wt%: water is 1:10:16, that is, the acid concentration in the nickel-chromium alloy etchant is increased.

[0087] The metallographic microscope photos observed in this comparative example are as follows Fig.10As shown, it can be seen that the increase in acid concentration in the nickel-chromium alloy etchant will lead to excessive corrosion of the metallographic structure of the nickel-chromium alloy and corrosion of part of the grain boundaries. The metallographic structure display effect of the nickel-chromium alloy in this comparative example is poor.

[0088] Comparative Example 2

[0089] This comparative example provides a method for displaying grain corrosion of a nickel-chromium alloy. Compared with Example 1, the only difference is that the formula of the nickel-chromium alloy etchant used for chemical corrosion is adjusted, and the volume ratio of hydrofluoric acid with a concentration of 40wt%: nitric acid with a concentration of 65wt%: water is 1:10:24, that is, the acid concentration in the nickel-chromium alloy etchant is reduced.

[0090] The metallographic microscope photos observed in this comparative example are as follows Fig.11 As shown, it can be seen that the reduction of the acid concentration in the nickel-chromium alloy etchant will result in the grain boundaries of the metallographic structure of the nickel-chromium alloy not being displayed at all, and the metallographic structure display effect of the nickel-chromium alloy in this comparative example is poor.

[0091] In summary, the present invention provides a nickel-chromium alloy etchant and a method for displaying grain corrosion of nickel-chromium alloy, wherein the nickel-chromium alloy etchant comprises a mixed solution of hydrofluoric acid, nitric acid and water, and the volume ratio of hydrofluoric acid: nitric acid: water is 1: (9-11): (18-22). When the nickel-chromium alloy etchant is used for chemical corrosion, the grains are clearly displayed, the metallographic display range is wide, the product analysis is more accurate, the process is stable and simple and can be reused, the detection time is short, the results can be obtained quickly, and the generation of defective products is effectively avoided; in particular, when the display method of embodiments 1-3 is used, the product grain display is clearer, which is better than other ratios.

[0092] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0093] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0094] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0095] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A nickel-chromium alloy etchant, characterized in that: The nickel-chromium alloy etchant includes a mixed solution of hydrofluoric acid, nitric acid and water, and the volume ratio of hydrofluoric acid: nitric acid: water is 1: (9-11): (18-22).

2. The nickel-chromium alloy etchant according to claim 1, characterized in that: The concentration of the hydrofluoric acid is 35-45 wt %, and the concentration of the nitric acid is 65-68 wt %.

3. A method for displaying grain corrosion of nickel-chromium alloy using the nickel-chromium alloy etchant according to claim 1 or 2, characterized in that: The grain corrosion display method comprises the following steps: The nickel-chromium alloy is sequentially subjected to grinding, electrolytic polishing, primary cleaning, chemical etching, secondary cleaning, and drying; wherein the nickel-chromium alloy etchant is used for the chemical etching.

4. The method for displaying grain corrosion according to claim 3, characterized in that: The grinding comprises: grinding the nickel-chromium alloy on 240# water-based sandpaper and 1000# water-based sandpaper in sequence, and using water as a wetting agent.

5. The method for displaying grain corrosion according to claim 3 or 4, characterized in that: The grinding time is 5-10 minutes.

6. The method for displaying grain corrosion according to any one of claims 3 to 5, characterized in that: The electrolyte used in the electrolytic polishing includes a mixed solution of ethanol, 2-butoxyethanol and perchloric acid, and the volume ratio of ethanol:2-butoxyethanol:perchloric acid is x:y:z=(0.65-0.75):(0.05-0.15):(0.15-0.25), x+y+z=1.

7. The method for displaying grain corrosion according to any one of claims 3 to 6, characterized in that: The voltage of the electrolytic polishing is 35-40V.

8. The method for displaying grain corrosion according to any one of claims 3 to 7, characterized in that: The electrolytic polishing time is 50-100s.

9. The method for displaying grain corrosion according to any one of claims 3 to 8, characterized in that: The chemical corrosion comprises: using the nickel-chromium alloy etchant, dropping it on the electrolytic polishing area of ​​the nickel-chromium alloy, and leaving it for 60-90 seconds.

10. The method for displaying grain corrosion according to any one of claims 3 to 9, characterized in that: The grain corrosion display method comprises the following steps: The nickel-chromium alloy is sequentially subjected to grinding, electrolytic polishing, primary cleaning, chemical etching, secondary cleaning, and drying; The polishing comprises: polishing the nickel-chromium alloy on 240# water-based sandpaper and 1000# water-based sandpaper in sequence, using water as a wetting agent, and the polishing time is 5-10min; the electrolyte used in the electrolytic polishing comprises a mixed solution of ethanol, 2-butoxyethanol and perchloric acid, and the volume ratio of ethanol: 2-butoxyethanol: perchloric acid is x:y:z=(0.65-0.75):(0.05-0.15):(0.15-0.25), x+y+z=1; the concentration of the ethanol is 95wt%, and the concentration of the perchloric acid is 30wt%; the voltage of the electrolytic polishing is 35-40V, and the time is 50-100s; the chemical corrosion adopts the nickel-chromium alloy etchant; the chemical corrosion comprises: using the nickel-chromium alloy etchant, dripping it on the electrolytic polishing area of ​​the nickel-chromium alloy, and staying for 60-90s.

Citation Information

Patent Citations

  • Nickel-chromium alloy metallographic corrosion solution and corrosion method

    CN104513985A

  • Metallographic-phase corrosive liquid and corrosion method for austenite resisto

    CN106124392A

  • Nickel-chromium alloy etching agent, and metallographic structure display method of nickel-chromium alloy

    CN106501058A

  • Electrochemical corrosive agent for displaying SLM molded IN 718 nickel-based high-temperature alloy metallographic structure and using method thereof

    CN111118592A

  • Crystal grain corrosion and display method of 304 stainless steel

    CN118376616A